2008
DOI: 10.1007/s00011-007-7089-z
|View full text |Cite
|
Sign up to set email alerts
|

Gastric damage induced by different doses of indomethacin in rats is variably affected by inhibiting iNOS or leukocyte infiltration

Abstract: Indomethacin at a dose of 20 mg.kg(-1), but not at 5 mg.kg(-1), induced gastropathy dependent on neutrophil infiltration and iNOS-generated NO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Experimental evidence in animals and humans suggests that nitric oxide contributes to NSAID‐induced ulcerogenesis via generation of iNOS 57–59 or a decrease in cNOS. NSAIDs have been shown to increase endothelin‐converting enzyme‐1 (ECE‐1) activity, thereby upregulating endothelin‐1 (ET‐1), which suppresses cNOS and endothelial nitric oxide leading to loss of mucosal integrity in rats 60 .…”
Section: Systemic Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental evidence in animals and humans suggests that nitric oxide contributes to NSAID‐induced ulcerogenesis via generation of iNOS 57–59 or a decrease in cNOS. NSAIDs have been shown to increase endothelin‐converting enzyme‐1 (ECE‐1) activity, thereby upregulating endothelin‐1 (ET‐1), which suppresses cNOS and endothelial nitric oxide leading to loss of mucosal integrity in rats 60 .…”
Section: Systemic Effectsmentioning
confidence: 99%
“…demonstrated that iNOS deficient mice had less severe gastric damage following indomethacin administration than wild‐type mice. Moreover, wild type mice treated with N G ‐nitro‐L‐arginine methyl ester (L‐NAME), a NOS inhibitor, at doses that inhibited iNOS, or a specific iNOS inhibitor also showed less damage 40, 59 . In contrast, Schmassmann et al.…”
Section: Systemic Effectsmentioning
confidence: 99%
“…Neutrophil activation and infiltration are crucial in the pathogenesis of NSAID-induced gastric inflammation and oxidative stress (Jainu and Shyamala Devi, 2005;Krawisz et al, 1984;Souza et al, 2008). Activating neutrophils results in the expression of proinflammatory genes and the overproduction of proinflammatory mediators, including TNF-a and IL-1b, and initiates an inflammatory response (Jaeschke and Hasegawa, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of neutrophils activation and their infiltration into gastric mucosa may be sesamol's anti-inflammatory and antioxidative mechanism. Neutrophil activation and infiltration are crucial in the pathogenesis of NSAID-induced gastric inflammation and oxidative stress (Souza et al, 2008). Activating neutrophils results in the expression of proinflammatory genes and the overproduction of proinflammatory mediators, including TNF-α and IL-1ß, which initiates an inflammatory response (Jaeschke & Hasegawa, 2006).…”
Section: Artichoke Leaf Extractmentioning
confidence: 99%